Diseño de instrumento FODA para el diagnóstico estratégico de la escuela profesional de educación secundaria en estudiantes del quinto nivel de la facultad de ciencias de la educación y humanidades Iquitos 2021 - Oliveira Ríos, Juan Orlando (2022)
Designing the SWOT analysis instrument for the strategic diagnosis of the Professional School of Secondary Education in students of the fifth level of the Faculty of Education Sciences and Humanities of the National University of the Peruvian Amazon located in Iquitos in the year 2021, has been the main objective to achieve with this research. The type of research was projective and the comprehensive level, with a bivariate, field design and its transversal temporality. The population and sample in the study were 71 fifth-level students of the Faculty. The data collection instruments have been validated by expert judgment on the research topic. The results show that the design level of the SWOT instrument in its dimensions: strategic axis of comprehensive training; of research and university social responsibility, is for 53.5% of the students subject to the study of good level and for 46.5% of average level, with which the hypothesis proposed for the investigation is also demonstrated.